2015
DOI: 10.1016/j.adolescence.2015.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary behavior, depressed affect, and indicators of mental well‐being in adolescence: Does the screen only matter for girls?

Abstract: The study investigated the effects of sedentary behavior (SB) on mental well-being and examined differences between screen-based (sSB) and non-screen-based sedentary behaviors (nSB) separately by gender. In a total sample of 1296 students (609 girls) aged 12 e17 (m ¼ 13.7, SD ¼ 0.67), SB, depressed affect, self-esteem, physical self-concept, general self-efficacy and physical activity were assessed through self-administered questionnaires. Among girls, lower scores in self-esteem, physical self-concept as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 40 publications
2
45
0
3
Order By: Relevance
“…Increased screen time has been associated with poorer mental health among adolescents [ 21 , 22 , 37 ], potential mechanisms underlying such associations include: 1) negative effects of sedentary behavior on body composition [ 37 ]; 2) psychosocial and psychological effects, as media use via the internet provides adolescents with diverse opportunities for comparing themselves with others. Discrepancies between these publicized ideals and the self could cause social pressure and mental health problems [ 59 ]; 3) screen time may negatively affect sleep [ 60 ], which might have unfavorable effects on mental health [ 5 ]; 4) screen time may displace physical activity [ 61 ], resulting in loss of beneficial effects of exercise on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Increased screen time has been associated with poorer mental health among adolescents [ 21 , 22 , 37 ], potential mechanisms underlying such associations include: 1) negative effects of sedentary behavior on body composition [ 37 ]; 2) psychosocial and psychological effects, as media use via the internet provides adolescents with diverse opportunities for comparing themselves with others. Discrepancies between these publicized ideals and the self could cause social pressure and mental health problems [ 59 ]; 3) screen time may negatively affect sleep [ 60 ], which might have unfavorable effects on mental health [ 5 ]; 4) screen time may displace physical activity [ 61 ], resulting in loss of beneficial effects of exercise on mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Suchert et al24 assessed effects of sedentary behaviour, depressed affect, self-esteem, physical self-concept, general self-efficacy and physical activity. Among girls, lower scores in self-esteem and general self-efficacy were associated with higher screen-based sedentary behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Gender is a common line of investigation in technology‐related research, with known differences for engagement style and frequency and duration of use of digital media among boys and girls (McFarlane, et al ., 2000; McFarlane, Sparrowhawk, & Heald 2002). Gender differences are more pronounced and are typically studied for older age groups in relation to digital games (eg, Nietfeld, Shores, & Hoffman, ) and social media engagement (eg, Suchert, Hanewinkel, Isensee, & Läuft Study Group, ). However, a national survey carried out by Ofcom in 2014 in the UK showed that there are some gender differences in media use even at a very young age: 30% of boys aged 3–4 years use a handheld/portable games player, compared to 21% girls aged 3–4 years.…”
Section: Children's Gendermentioning
confidence: 99%